Systematic review protocol: following PRISMA guide from Cochrane to generate evidence as treatment effect of pharmaceutical care for hypertension in primary care - Maurílio de Souza Cazarim; Tiago Marques dos Reis; Estael Luzia Coelho da Cruz-Cazarim; Leonardo Régis Leira Pereira (Universidade de São Paulo, 2021)
Pharmaceutical care (PC) is in the implementation process in Brazil and Latin America. Synthesis of evidence has been requested for monitoring and evaluating the process regarding the treatment effect. The objective is to build and disseminate a systematic review protocol to make a standard for updating results from pharmaceutical care for hypertension and for other diseases. This is a protocol for systematic review studies regarding a real example of a protocol reasoned in pharmaceutical care for hypertension in primary care. This protocol was delineated grounded in the Cochrane Handbook. Descriptors and words were defined using MeSH (Medical Subject Headings), DeCS (Descriptors in Health Sciences) and Emtree thesaurus, and the search was performed in English, Spanish and Portuguese, without filters, up to March, 27th, 2017. The results were structured in the PRISMA flowchart. Results found from all databases were: the Cochrane Library (n= 202); PubMed (n= 2608); LILACs (n= 909); Embase (n= 1653); Scopus (n=1298); IPA (n=967); and Web of Sciences (n=435). From these, 1688 were duplicate articles. The content of this paper can aid the constant monitoring of pharmaceutical care implementation and contribute to the improvement of the quality and evidence levels of published studies.